Research Title: The Effect of Financial Risk on the Profitability of Manufacturing Companies Listed on the IDX in 2020-2024 - Kharimah Murni; Achmad Hizazi; Ratih Kusumastuti (Nomico, 2025)
This study analyzes the effect of financial risk, as measured by the Debt to Asset Ratio and Debt to Equity Ratio, on profitability (Return on Assets - ROA) in manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2024 period. Using multiple linear regression with SPSS software on 95 observations, descriptive statistics show an average DAR of 0.3686, DER of 0.8498, and ROA of 0.0953. The results of the simultaneous test (F test) show a Sig. value of 0.000, indicating that DAR and DER together have a significant effect on ROA. The coefficient of determination (Adjusted R Square) of 0.289 indicates that 28.9% of the variation in ROA is explained by the model. Partially (t-test), DAR (X1) has a negative and significant effect (Sig. 0.000, coefficient -0.325) on ROA, while DER (X2) has a positive and significant effect (Sig. 0.000, coefficient 0.074) on ROA. These findings highlight the complexity of the relationship between financial risk and profitability in the manufacturing sector.